Human motion sensing and recognition : a fuzzy qualitative approach /: a fuzzy qualitative approach. (2017) - (Professor of Intelligent Systems), Liu, Honghai; Ju, Zhaojie; Ji, Xiaofei; Chan, Chee Seng; Khoury, Mehdi
No abstract available